New trends of progestins treatment of endometriosis. (November 2014) - Angioni, Stefano; Cofelice, Vito; Pontis, Alessandro; Tinelli, Raffaele; Socolov, Razvan
Abstract The management of endometriosis with OC or progestins is generally safe, effective and well-tolerated and should constitute the first line of medical treatment in symptomatic patients who do not want to have children. Progestins, synthetic progestational agents, have been used in the management of symptomatic endometriosis both as primary therapy and as an adjunct to surgical time. A variety of oral agents have been employed in this regard and investigators have demonstrated differing degrees of benefit. The lack of a standardized instrument to evaluate painful symptoms makes comparative analysis more difficult. Concern about efficacy and side effect has pushed the research on the development of new well-tolerated drugs and to develop new administration routes to minimize general side effects. Aim of the present review is to present the results of clinical studies on new trends of progestins in the treatment of endometriosis.